Tourist Satisfaction as a Pathway between Quality Tourism Experience and Revisit Intention in Nepal - Puri, Ram Kumar; Subedi, Manoj (Nepalese Journal of Hospitality and Tourism Management, 2026)
This study examined role of quality tourism experience in shaping both tourists’ satisfaction level and their intention to visit again. Descriptive and causal research designs were used in this study. To obtain quantitative data about international visitors to Nepal who had stayed a minimum of five nights, a cross-sectional survey was administered to collect data from 437 valid responses. Descriptive statistics, correlation analysis, and structural equation modeling were then used to analyze the data and examine direct, indirect, and mediating relationships among the variables. Results indicate that the quality of the tourist experience significantly influenced tourists’ revisit intention, while there is no mediating effect between tourists’ satisfaction level on this relationship, nor is there a relationship between tourists’ satisfaction with the experience and repeat visit. Traditional satisfaction factors such as residents’ hospitality, and the role of intermediaries - contributed to overall satisfaction but have little impact on revisit intention. The conclusion is that for destinations like Nepal where experience is the key driver of tourism, intrinsic quality attributes associated with the cultural, adventure and natural tourism experiences are greater motivators for return visitation than general service satisfaction. Based on this conclusion, tourism strategies should focus on enhancing the experiential attributes, rather than just enhancing the quality of traditional service offerings. These findings shows that satisfaction, as the main mediator in the traditional model of the relationship between service quality and loyalty, is in fact only one path of many, through which experiential factors can influence tourist behavior.